Analisis Karya Kecerdasan Buatan Italian Brainrot Dalam Perspektif Undang-Undang Hak Cipta - Aulia Khansa Nabila; Yudho Taruno Muryanto (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This research aims to analyze one of the works produced by artificial intelligence, specifically Italian Brainrot, in the field of image-based creations. The use of artificial intelligence technology brings its own challenges in the field of copyright law, as it gives rise to a fundamental legal uncertainty regarding whether works generated by artificial intelligence can be categorized as "creations" protected by copyright under Law Number 28 of 2014 on Copyright. The method used is normative juridical with a literature study approach, referring to Law Number 28 of 2014 on Copyright and other related regulations. The research findings indicate that works produced entirely by the Italian Brainrot artificial intelligence cannot obtain copyright protection in Indonesia. This is because Italian Brainrot's AI-generated works do not meet the requirements for a creation to be eligible for copyright protection, namely originality, creativity, and embodiment. Italian Brainrot has not fulfilled the requirement of human authorship and human creativity, and therefore cannot yet obtain copyright protection.